Gastroprotective and antisecretory effects of Ailanthus excelsa (Roxb) - Melanchauski, Larissa S. [UNESP]; Broto, Ana Paula G. S. [UNESP]; Moraes, Thiago M. [UNESP]; Nasser, Ana Lucia M. [UNESP]; Said, Ataa; Hawas, Usama W.; Rashed, Khaled; Vilegas, Wagner [UNESP]; Hiruma-Lima, Clélia Akiko [UNESP] (Springer Tokyo, 2010)
Ailanthus excelsa (Roxb), an Egyptian medicinal species highly important for treating numerous diseases, was investigated against experimentally induced gastric ulcer in rodents. We evaluated the gastroprotective effect of four extracts (petroleum ether, diethyl ether, chloroform, and methanol) of A. excelsa bark by using the ethanol-induced gastric lesion model. The pretreatment of animals with methanolic, petroleum ether, and chloroformic extracts (100 mg/kg, oral (p.o.)) from A. excelsa significantly reduced gastric lesion induced by ulcerogenic agent (56, 47, and 70%, respectively) when compared with animals pretreated with vehicle. However, the diethyl ether pretreatment led to the least gastric lesion damage (83%), similar to the standard antiulcer drug, cimetidine, at the same dose (100 mg/kg, p.o.). The lower effective dose of diethyl ether extract, as well as cimetidine, given by intraduodenal route, significantly increased the pH values and reduced the acid output of gastric juice. Sterols, triterpenes, and quassinoids are present in the diethyl ether extract of A. excelsa stem bark, which presented the best gastroprotective action among the studied extracts. Our study confirmed the traditional indications of A. excelsa for the treatment of gastric ulcer.
Keywords: Ailanthus excelsa; Gastroprotective action; Quassinoids